Study on Postgraduate Student Preferred / Dislike Teaching/Learning Techniques: A Case Study of a Private University in Malaysia - Raemah Abdullah Hashim,; Abdul Razak Habib,; Zulaika Zakariah,; Wardah Mohamad, (2014)
This paper examine preferred / dislike teaching/learning techniques among postgraduate student at a Malaysian university. Past studies had indicated the promotion of students’ “graduateness”, responsibility lies in the hand of teachers who need to know what are in the mind of student with regards to their most preferred or non preferred learning and teaching style. 57 returned questionnaires were accepted and coded, and subject to further analysis with a response rate of 73 percent from the private university. The result revealed that the highest ranked technique most preferred by the students was “interactive lecture by instructor and the most dislike technique was formal lecture by instructor. Significant finding was that though there were some differences within the different disciplines, some commonalities seem to be present. Future study should consider alternative modes of enquires such as employing the longitudinal method of data collection design and a nationwide survey covering samples from the whole population of the higher institutions of learning in Malaysia that would be more significant in making generalizations .